Energy and Exergy Analysis on a Novel Solar-Air Dual-Source Vapor Injection Heat Pump Air-Conditioner for the Electric Bus - Zhang, Hong; Liu, Qian; Yang, Lichen (Frontiers in Energy Research, 2022)
A novel solar-air dual-source vapor injection heat pump air-conditioner for the electric bus is proposed, aiming to enhance the system heating performance and increase the vehicle endurance. Three working modes are designed for the proposed system, including solar-air dual-source heating mode, air source heating mode, and cooling mode. The system heating performance is explored by the simulation approach. Compared with the conventional vapor injection heat pump, the proposed system averagely enlarges the heating capacity and efficiency by 17.0% and 21.2%, respectively, under the considered evaporating temperature range (−25∼0°C) by utilizing the solar energy. Moreover, the two systems possess the optimal intermediate pressures to achieve the maximal heating efficiency. The system performance comparison under the two heating modes indicates that the dual-source mode is preferred except for the extremely low or no solar radiation situation. The exergy analysis shows that more than half of the system total exergy input is destructed in the solar collector, which grows by 111.4% as the solar radiation intensity increases by 300 W m−2; thus, the system exergy efficiency decreases as the solar radiation enhances, although the system heat exergy output shows a growth tendency. The component irreversibility analysis on the proposed system is also conducted, aiming to explore the reason for the system exergy performance variation and the irreversibility distribution rule. At last, the exergy flow situations of the proposed system and the conventional system are contrastively analyzed. The exergy performance comparison indicates that under the given condition the proposed system can improve the exergy output by 20.2% and decrease the electricity consumption by 4.5% compared with the conventional system.